Human rights - Palma, Tina Monzon; Lu, Sonny; Garcia, C. (Velez this week, 1989)
Identifies the type of human rights and examines the conditions in Philippne government and society which give rise to violation of these rights. Airs divergment views of victims, advocates, academics and alleged violators.